2012
DOI: 10.1073/pnas.1117551109
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for receptor sharing and activation by interleukin-20 receptor-2 (IL-20R2) binding cytokines

Abstract: Interleukin 20 (IL-20) is a pleotropic IL-10 family cytokine that protects epithelial surfaces from pathogens. However, dysregulated IL-20 signaling is implicated in several human pathologies including psoriasis, rheumatoid arthritis, atherosclerosis, and osteoporosis. IL-20, and related cytokines IL-19 and IL-24, designated IL-20 subfamily cytokines (IL-20SFCs), induce cellular responses through an IL-20R1/IL-20R2 (type I) receptor heterodimer, whereas IL-20 and IL-24 also signal through the IL-22R1/IL-20R2 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
71
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(75 citation statements)
references
References 31 publications
3
71
1
Order By: Relevance
“…10 Type I IFNs in both mammals and fish are structurally distinct from the remainder of the class II cytokines, with the most notable difference being the F helix, which is straight in type I IFNs, while it bends almost 901 in all other class II cytokines. 4,7,10,11 An expansion of the class II cytokine system seems to have taken place largely during the Cambrian explosion when vertebrates diverged from basal chordates. In the protochordate Ciona intestinalis, two proteins showing similarities to class II cytokines receptors have been found, 2 although the ligands are still unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Type I IFNs in both mammals and fish are structurally distinct from the remainder of the class II cytokines, with the most notable difference being the F helix, which is straight in type I IFNs, while it bends almost 901 in all other class II cytokines. 4,7,10,11 An expansion of the class II cytokine system seems to have taken place largely during the Cambrian explosion when vertebrates diverged from basal chordates. In the protochordate Ciona intestinalis, two proteins showing similarities to class II cytokines receptors have been found, 2 although the ligands are still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Structures have been reported for several human members of this family, namely IL-22, IL-10, IL-19, IL-20, several type I IFNs, type II IFNs and one type III IFN (IFNl3). [4][5][6][7][8][9][10] They are all a-helical bundle-like proteins with six structural elements named A to F. Elements A, C, D, E and F are a-helices, whereas element B is more variable and contains a b-sheet harpin 7,10 in some members. The protein core is formed by four helices (A, C, D and F) in up-up-down-down orientation.…”
Section: Introductionmentioning
confidence: 99%
“…Because the ternary IL-10 receptor complex could not be crystallized so far, only the structure of IL-10 in complex with its receptor chain 1 (IL-10R1) is known as of today. However, the structure of the related IL-20 receptor complex was solved recently (73). IL-10 and IL-20 belong to the same cytokine family and have a high structural similarity.…”
Section: Discussionmentioning
confidence: 99%
“…IL-20R2 is a cytokine receptor that is involved in signaling by the IL-10 family cytokines, IL-19, IL-20, and IL-24. 49 IL-20 and IL-24 can signal through both heterodimeric receptor types, but IL-19 signals only through the type I complex (Fig. 1).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that IL-20R2 binds to the ligand, which then recruits IL-20R1 and heterodimerization occurs. 30 Since T104M sits at a site critical for ligand binding, 49 it is likely that cytokine binding and heterodimerization is disrupted. The T104M mutation could disrupt signaling that is initiated by all 3 cytokines.…”
Section: Discussionmentioning
confidence: 99%